Do discurso de isolamento a uma experiência de solidão - Tatit, Isabel (2012)
This paper makes a distinction between the discourse of isolation and feelings of loneliness. Numerous contemporary discourses about loneliness pathologize it, based on universalizing approaches, and submit it to healing procedures. Such discourses reproduce imperatives of happiness and self-sufficiency, transforming the experience of loneliness into something to be cut off from the social field. In the clinic, patients who experienced territorial displacement and consequent distancing from close relationships express feelings of self-sufficiency, which leads us to believe that their discourses of isolation are highly permeable to the actions of the discourses of autonomy widespread in society. Throughout this research, the signifier of loneliness episodically emerged as an expression of the subject s unease in the gaps of the discourse of isolation. Thus, when presented as a counterpoint to the dominant discourse, loneliness may reflect an ethical experience by expressing the uniqueness of the subject. Thus, when presented as a counterpoint to the dominant discourse, loneliness may reflect an ethical experience by expressing the uniqueness of the subject